PERHITUNGAN NILAI DOSIS DAN KONTRAS CITRA COMPUTED RADIOGRAPHY (CR) DENGAN VARIASI KETEBALAN DAN KOMBINASI JENIS FILTER - Dessy Dian Monita Pardede; Evi Setiawati (Youngster Physics Journal, 2014)
The research about calculation of dose values and image contrast computed radiography has done with thickness variation and combination type filter.  Additional filters are ideal able to absorb all of the energy is low and continuing high energy X-rays. Materials filters are often used in radiodiagnostic is Aluminum (Al). This researc used material such aluminum (Al), stainless steel (Ss), Zinc (Zn) and combine the filter to get low dose withhigh contrast quality.The thickness of the filter are 0.5 mm, 1 mm, 1.5 mm, 2 mm of the three types of filter material with maximum combination thickness of the filter material is 2 mm.  Irradiation performed with a Shimadzu brand X plane by a factor of 3.55 eksposi 50 kVp and mAs with an area of 15 x 15 cm field using the object stepwedge. Dose measurements performed with the detector R100B while the contrast of the image is determined by calculating the gray value of image by using the technique of ROI (Region of Interest) on any object thickness stepwedge.Measurement of dose and image contrast value obtained some filters that generate a low dose with high image contrast. The use of one type of filter that produces low-dose and high image contrast are on filters Al 0.5 mm, Al 1 mm, Al 1.5 mm, Al 2 mm, Zn 0.5 mm, Zn 1 mm, Ss 0.5 mm. While the use of a combination of the type of filter that produces a low-dose and high image contrast value are on 0.5 mm Al + Zn 0.5 mm, 1 mm Al + Zn 0.5 mm, 0.5 mm Al + 0.5 mm Ss, 1.5 mm Al + Zn 0.5 mm, 1.5 mm Al + 0.5 mm Ss and  Ss 0.5 mm + 0.5 mm Zn. By combining this type of filter then obtained a lower dose compared with only one type of filter material. Keywords: Radiodiagnostic, additional filters, Dose, Gray value, Image contrast radiography, Computed Radiography (CR)